2021
DOI: 10.3390/antib10040045
|View full text |Cite
|
Sign up to set email alerts
|

Fc-Independent Protection from SARS-CoV-2 Infection by Recombinant Human Monoclonal Antibodies

Abstract: The use of passively-administered neutralizing antibodies is a promising approach for the prevention and treatment of SARS-CoV-2 infection. Antibody-mediated protection may involve immune system recruitment through Fc-dependent activation of effector cells and the complement system. However, the role of Fc-mediated functions in the efficacious in-vivo neutralization of SARS-CoV-2 is not yet clear, and it is of high importance to delineate the role this process plays in antibody-mediated protection. Toward this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…In contrast, sotrovimab increases binding to FcRn by LS modification (Gupta et al, 2021). In the absence of Fc receptor binding ability, there is a report that the therapeutic effect is decreased (Chan et al, 2021) and others that it is not significantly changed (Noy-Porat et al, 2021), and a consensus has not been established. In this context, our antibodies demonstrated the therapeutic effects in hamsters and macaques at doses of at least 5 to 7 mg/kg, without increased viral uptake by ADE (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, sotrovimab increases binding to FcRn by LS modification (Gupta et al, 2021). In the absence of Fc receptor binding ability, there is a report that the therapeutic effect is decreased (Chan et al, 2021) and others that it is not significantly changed (Noy-Porat et al, 2021), and a consensus has not been established. In this context, our antibodies demonstrated the therapeutic effects in hamsters and macaques at doses of at least 5 to 7 mg/kg, without increased viral uptake by ADE (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…There is an ongoing discussion concerning the importance and the potential risk of having active Fc activity in antibodies targeting SARS-CoV-2. On one hand, Fc effector functions have been reported to be essential for optimal therapeutic protection against SARS-CoV-2 [ 218 , 240 , 284 286 ]; on the other hand, at least in some cases, significant protection was achieved in animal models independent of Fc functionality, suggesting that antibody Fab-dependent neutralization in absence of Fc function was sufficient to eliminate the virus [ 287 ]. Additionally, Fc engagement of FcγRIIIa has been correlated with disease severity in COVID-19 patients [ 288 , 289 ] and Fc engagement of FcγRIIa/b is a potential risk of increasing viral infection via an ADE mechanism [ 221 , 288 ].…”
Section: Anti-sars-cov-2 Igg Antibodiesmentioning
confidence: 99%
“…While it has been demonstrated that antibodies to SARS-CoV-2 can neutralize the virus in the absence of Fc functionality [ 287 ], it has become clear that Fc activity enhances the ability of IgGs to neutralize SARS-CoV-2. Several groups have recently demonstrated using in vitro and/or in vivo experiments that an intact Fc, which interacts with immune cells such as NK cells to promote ADCC and phagocytes to promote antibody dependent cellular phagocytosis (ADCP), is required for optimal anti-SARS-CoV-2 antiviral activity [ 218 , 284 , 291 ], just as it is with HIV [ 292 , 293 ].…”
Section: Anti-sars-cov-2 Igg Antibodiesmentioning
confidence: 99%
“…Another RBM antibody, COV2–2050 ( Zost, Gilchuk, Case, et al, 2020 ), displayed reduced protection in a mouse model of SARS-CoV-2 infection by introduction of the LALA-PG (L234A, L235A, P329G) Fc mutations which eliminate Fc ɣ R binding ( Lo et al, 2017 ; Winkler et al, 2021 ). The importance of these functions for ultra potent neutralizing RBM antibodies is unclear, however, as C144 and other ACE2-blocking antibodies can prophylactically and therapeutically protect mice from SARS-CoV-2 challenge by neutralization ( Noy-Porat et al, 2021 ; Schäfer et al, 2020 ). In general, it seems that Fc effector functions may be more important for protection by less-potently neutralizing antibodies or with delayed onset of therapy ( Chan et al, 2021 ; Winkler et al, 2021 ).…”
Section: Monoclonal Antibodies Targeting the Receptor-binding Domain ...mentioning
confidence: 99%